Cardiac Dysfunction Among Ugandan HIV-Infected Children on Antiretroviral Therapy - Namuyonga, Judith; Lubega, Sulaiman; Musiime, Victor; Lwabi, Peter; Lubega, Irene (The Pediatric infectious disease journal, 2016)
Despite effective antiretroviral therapy (ART), HIV-infected children on treatment have been observed to have cardiac abnormalities. We sought to determine the prevalence, types and factors associated with cardiac abnormalities among HIV-infected Ugandan children on combination ART. Methods—We carried out a cross-sectional study from July 2012 to January 2013, at Joint Clinical Research Centre among HIV infected children aged 1 to 18 years. Cardiac abnormalities were assessed using electrocardiography (EKG) and echocardiography. CD4 counts, viral load and complete blood count were performed at enrollment. The prevalence of cardiac abnormalities was determined using simple proportions with the associated factors ascertained using logistic regression. Results—Among 285 children recruited, the median (IQR) age was 9 (6, 13) years, 54% were female; 72% were on first line cART. Their mean (±sd) CD4 count was 1092 (±868.7) cells/mm3; median (IQR) viral load was 20 (20, 76) copies/ml. 94% had adherence to ART of more than 95%. Cardiac abnormalities were detected in 39 (13.7%) children. The most common abnormalities by EKG and echocardiography were non specific T-wave changes (4.6%) and pericardial disease (thickened pericardium with or without pericardial effusion) (2.8%), respectively. No factor assessed was found to be significantly associated occurrence of cardiac dysfunction. Conclusions—The prevalence of cardiac dysfunction among the HIV-infected children on ART was 13.7 % which was high, with non specific T wave changes and pericardial disease being the most frequent abnormalities observed. No factor assessed was found to be associated with cardiac dysfunction.
Keywords: HIV; Africa; Children; Cardiac dysfunction; Antiretroviral therapy